Application of Simulated Annealing for Color Pattern Recognition to Hybrid Optoelectronic Joint Transform Correlator - Chen, Chulung; Hsu, Yunghsin; Fu, Sihliang; Liao, Weichih; You, Chengsyuan (European Journal of Applied Sciences, 2016)
For invariant pattern recognition, a method using simulated annealing algorithm is introduced. Near optimal quantized reference functions are designed to be displayed on liquid crystal spatial light modulators. Mach-Zehnder joint transform correlator is adopted as the system for recognition of color targets. From numerical results, the optoelectronic pattern recognition system with simulated annealing algorithm shows a promising capability.